Systematic Assessment of Climate Risk and Sustainability-Related Disclosure Standards - Kumar, Deepak (Digital Repository of Theses - SSBM Geneva, 2025)
Sustainability reporting is evolving significantly in light of growing climate change concerns. The research examines sustainability-related disclosure across major frameworks and standards and their usage by stakeholders, including disclosing companies, regulators, investors, and assurance providers. The research evaluates the alignment and effectiveness of major reporting frameworks across dimensions of size, emission level of sectors, and the market context and identifies the theoretical motivations. The research utilizes a mixed-methods approach that includes quantitative analysis, surveys, statistical analysis, and interviews. The approaches include content analysis of reporting frameworks, analysis of sustainability reports from various sectors, surveys, and in-depth interviews with key stakeholders. The research identifies two primary themes for sustainability disclosure. The first theme, referred to as the sustainability theme, focuses on the companies’ sustainability practices consisting of environmental, social, and governance (ESG) areas, and the Global Reporting Initiative (GRI) is based on this theme. The second theme, referred to as the climate theme, focuses on the impact of climate-related changes on the financials of firms, and the International Financial Reporting System (IFRS) S2 is based on this theme. There is very little overlap between the two themes, although there are ongoing efforts to make these reporting frameworks and standards interoperable. While ISSB creates a global baseline, ISSB emphasizes financial materiality and climate risk disclosures, which makes this popular among investors. GRI focuses on broader sustainability materiality relevant to multiple stakeholders. The research concludes that metrics and targets are comparable within a sector. However, the requirements related to governance, strategy, and risk management and the interconnectedness of the four pillars under ISSB lack clarity and comparability. The assurance mechanism requires robustness except for the metrics and targets pillar and linkages to sustainable finance. The research concludes that size, sector, and market context have a clear impact on the maturity of disclosures and assurance-related practices. In terms of theoretical and practical implications, this research contributes to legitimacy and stakeholder theory by demonstrating regulatory pressure and stakeholder expectations driving framework adoption. The research highlights ongoing challenges in framework harmonization and concludes that sustainability-related disclosures still require a clear definition and measurement to achieve the required objectives. Keywords: sustainability, sustainability reporting, sustainability framework, climate risk, physical risk, transition risk, sustainability reporting standards, materiality assessment, sustainability assurance.